Relationship between abdominal aortic calcification with 30 days postoperative outcome in patient underwent colorectal surgery - Ali, Ahmad Adham (2019)
Background: Anastomotic leakage in colorectal surgery remains a devastating complication with its associated post-operative morbidity and mortality. Various risk factors have been described, such as ASA score, left sided anastomosis or emergency surgery. However, the rate remained high. Thus, risk factor for colorectal anastomotic leakage and associated postoperative morbidities remain incompletely understood and yet to be discovered. This study describes the use of abdominal aortic calcification score as a prognostic factor for colorectal anastomotic leakage and its associated post-operative morbidities. Methods: This is a retrospective review of patient clinical data at Hospital Universiti Sains Malaysia from January 2012 until June 2017. Cases were all patient who underwent colorectal surgery with left sided anastomosis including benign and malignant disease performed in elective or emergency setting. All cases either open or laparoscopic approach were included in this study. Abdominal aortic calcification score were determined by pre-operative CT scan and its association with early postoperative outcome (30 days) were analysed. Results: A total of 78 patients were included in this study in which 42 patients (53.8%) were female and 36 patients (46.2%) were male. The mean age of the subject is 56.47 years. Majority had been diagnosed with hypertension (HPT, 42.3 %) and diabetes mellitus (DM, 24.4%), while some others diagnosed with hyperlipidemia (HPL, 17.9%) and ischemic heart disease (IHD, 11.5%). Thirty two patients (41.0%) were ASA 1, 36 patients (46.2%) were ASA 2, while the other 10 patients (12.82%) were ASA 3. As for abdominal aortic calcification score (ACS), twenty-four patients (30.8%) has no aortic calcification (ACS score 0). Patient with a score of 1 were 37 patients (47.4%) while 17 patients (21.8%) had aortic calcification score of 2. There was significant association between hypertension (HPT) and ACS (p-value=0.002). There was also significant association between ASA score and ACS (p-value = 0.001). In our study, majority of subjects had no post-operative morbidity (48.7%) such as wound infection, atelectasis or even major post-operative morbidity such as sepsis and death. Thirty one patients (39.7%) had minor complications (Clavien Dindo grade 1&11) and 9 patients (11.6%) had major complications (Clavien Dindo grade 111 till V). However, there was no significant correlation between ACS with postoperative morbidity (p=0.921). Postoperative anastomotic leakage was diagnosed in 10 patients (12.8%). There was one postoperative mortality recorded. Otherwise, there was no significant relationship between ACS and anastomotic leakage (p = 0.572) Conclusion: This study demonstrates that abdominal aortic calcification score does not correlate with post-operative morbidity or influence the colorectal anastomotic leakage. However, future prospective study is suggested with a larger sample size.